Analysis of ion doping profiles in Yb-doped fiber preforms using laser-induced breakdown spectroscopy. Issue 2 (9th December 2015) - Li, Jiaming; Guo, Lianbo; Zhao, Nan; Chen, Qimeng; Wu, Baoye; Wang, Yibo; Li, Xiangyou; Li, Jinyan; Zeng, Xiaoyan; Lu, Yongfeng
Abstract : This study describes ion doping profiling in Yb-doped fiber preforms using laser-induced breakdown spectroscopy assisted by a self-adaptive median filter. Abstract : Ion doping profiles are one of the most important characteristics in Yb-doped fibers, but it is difficult to realize rapid, in situ, and online analysis. A laser-induced breakdown spectroscopy (LIBS) system was set up to analyze ion doping profiles in Yb-doped fiber preforms. However, laser-induced irregular cracking occurred on the preform surfaces and generated outliers in the Yb maps that affected the analytical results. An algorithm of a self-adaptive median filter (SAMF) was introduced to modify the maps. The results of LIBS mapping assisted by SAMF clearly described the doping profiles of a step-wise and a central dip. The energy dispersive X-ray spectroscopy (EDS) and the X-ray fluorescence (XRF) techniques were used to validate the analytical results. This study provides a rapid, in situ, and online approach for analysis of ion doping profiles in Yb-doped fibers.